2019
DOI: 10.29252/hehp.7.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Health Education Campaign (HEC) in the Field of Breast Cancer Screening in the North of Iran

Abstract: Use of the Health Education Campaign (HEC) in the Field of Breast Cancer Screening in the North of Iran[1] Breast cancer in Iran: Need for greater women awareness of warning signs and effective screening methods [2] Health beliefs about mammography and clinical breast examination among female healthcare providers in Tabriz health centers [3] Proapoptotic PUMA targets stem-like breast cancer cells to suppress metastasis [4] Breast cancer status in Iran: Statistical analysis of 3010 cases between 1998 and 2014 [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
3
1
0
1
Order By: Relevance
“…This finding is consistent with the results of the studies conducted by Awwad et al, Noman et al, Ibitoye et al, and Dadsetan et al and on learning knowledge from longitudinal data of mammograms to improving breast cancer risk prediction [ 22 – 25 ]. It is consonant with another study by Mohsenipouya et al, who aimed at investigating the use of educational intervention in breast cancer screening in northern Iran [ 26 ]. Also, it was consistent with the studies by Heidari et al, Sabeg et al, and Sadeghi et al [ 27 – 29 ].…”
Section: Discussionsupporting
confidence: 80%
“…This finding is consistent with the results of the studies conducted by Awwad et al, Noman et al, Ibitoye et al, and Dadsetan et al and on learning knowledge from longitudinal data of mammograms to improving breast cancer risk prediction [ 22 – 25 ]. It is consonant with another study by Mohsenipouya et al, who aimed at investigating the use of educational intervention in breast cancer screening in northern Iran [ 26 ]. Also, it was consistent with the studies by Heidari et al, Sabeg et al, and Sadeghi et al [ 27 – 29 ].…”
Section: Discussionsupporting
confidence: 80%
“…The research results regarding performing three breast cancer screening behaviors, including monthly breast self-examination, clinical examination by the midwife or physician and mammography, indicated that the rate of performing such three behaviors increased significantly in the intervention group compared to the control group (Regarding the clinical examination by the midwife or physician, considering that this examination should be done routinely once a year, the results of the study showed a significant increase in this examination, which was due to the fact that a number of women in the intervention group after ultrasound or mammography were determined to have breast cysts, and these women were examined once or even twice by the midwife or physician at intervals of 3 and 6 months). This study produced results which corroborate the findings of a great deal of the previous work in mammography by Khani Jeihooni et al [ 59 ], khalili et al [ 6 ]; the findings are consistent with data obtained from monthly breast self-examination, Bashirian et al [ 66 ], these results are in line with those of previous studies about monthly self- and clinical examination by Sheppard et al [ 61 ] and Mohseni et al [ 69 ]. However, the findings of the current study do not support the previous research given breast self-examination and mammography 2 months after the intervention [ 49 ].…”
Section: Discussionsupporting
confidence: 92%
“…The intention is a key factor in a person's readiness to perform a behavior. Researchers believe that the more people intend to perform a behavior, the more likely they perform that behavior[36, 65].The research results about performing three breast cancer screening behaviors, including monthly breast selfexamination, clinical examination by a midwife/physician, and mammography, indicated that the rate of performing such three behaviors increased signi cantly in the intervention group compared to the control group.The result was consistent with the results of studies by Khani Jeihooni et al about mammography [60], Shojae Zadeh et al [6], Bashirian et al about monthly breast self-examination [67], Sheppard et al [62], and Mohseni et al[70] about monthly self-and clinical examination, but the results were inconsistent with studies by Ghafari et al[11] about breast selfexamination and mammography two months after the intervention. The differences between the two groups after the educational intervention showed the effectiveness of the educational intervention based on the health action model (HAM).ConclusionImproving women's knowledge, attitude, and motivation can play important role in regular breast cancer screening behaviors.…”
supporting
confidence: 81%